Design principles of biochemical oscillators - Novák, Béla; Tyson, John J. (Nature reviews. Molecular cell biology, 2008)
Key Points Many physiological behaviours of cells are repeated periodically in time, such as hormone secretion, second messenger signalling, cell-division cycles and circadian rhythms. Oscillatory behaviour is a systems-level property of the interactions of genes, proteins and metabolites in the cell. All biochemical oscillators are characterized by negative feedback with time delay. Time delay can be due to a chain of intermediates between the 'cause' and 'effect' of the negative-feedback loop or to a positive-feedback loop in the network. For a biochemical reaction network to oscillate, the kinetics of the reactions must be sufficiently nonlinear and their timescales must be properly balanced, in quantitative terms that are predicted by theoretical analysis. These conditions are satisfied by various specific network topologies that provide the basis for a classification of biochemical oscillators. Biochemical oscillations are generated by complex interactions between genes, proteins and cellular metabolites and underlie many processes. Oscillatory behaviour is characterized by negative feedback with time delay, nonlinearity of the reaction kinetics and proper balancing of the timescales of opposing chemical reactions. Cellular rhythms are generated by complex interactions among genes, proteins and metabolites. They are used to control every aspect of cell physiology, from signalling, motility and development to growth, division and death. We consider specific examples of oscillatory processes and discuss four general requirements for biochemical oscillations: negative feedback, time delay, sufficient 'nonlinearity' of the reaction kinetics and proper balancing of the timescales of opposing chemical reactions. Positive feedback is one mechanism to delay the negative-feedback signal. Biological oscillators can be classified according to the topology of the positive- and negative-feedback loops in the underlying regulatory mechanism.